2019
DOI: 10.1055/a-0885-9943
|View full text |Cite
|
Sign up to set email alerts
|

Role of RF-amid Related Peptide-3 (RFRP-3) in Inhibitory Effect of Orexin A on Reproductive Function in the Animal Model of Male Wistar Rats

Abstract: Aims The aim of the present study is to examine the orexin A (OXA) signaling can leave any impact on the hypothalamic-pituitary-gonadal (HPG) axis and this impact can be relayed through the pathway of RF amide-related peptide-3 (RFRP-3, the mammalian ortholog of the avian gonadotropin-inhibitory hormone)/G-protein coupled receptor (GPR)-147 (RFRP-3 receptor) as a novel target for controlling of HPG axis in the male rats. Materials and Methods Male rats were categorized randomly into experimental groups inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Recent studies from intracerebroventricular (ICV) injection showed that orexin A decreased the relative expression of the GnRH gene while increasing the relative expression of RFRP-3 and GPR147 genes. This seems to imply that orexin regulation of the HPG axis occurs, at least in part, by affecting the RFRP-3/GPR147 system upstream of e230079 GnRH neurons (Hefshejanni & Khazali 2019), but further studies are needed.…”
Section: Potential Neuroendocrine Pathways That Transmit Metabolic Si...mentioning
confidence: 99%
“…Recent studies from intracerebroventricular (ICV) injection showed that orexin A decreased the relative expression of the GnRH gene while increasing the relative expression of RFRP-3 and GPR147 genes. This seems to imply that orexin regulation of the HPG axis occurs, at least in part, by affecting the RFRP-3/GPR147 system upstream of e230079 GnRH neurons (Hefshejanni & Khazali 2019), but further studies are needed.…”
Section: Potential Neuroendocrine Pathways That Transmit Metabolic Si...mentioning
confidence: 99%